Are trans‐complementation systems suitable for hepatitis C virus life cycle studies?. Issue 4 (14th February 2013) - Fournier, C.; Duverlie, G.; Castelain, S.
Summary: Complementation is a naturally occurring genetic mechanism that has been studied for a number of plus‐strand RNA viruses. Although trans ‐complementation is well documented for Flaviviridae family viruses, the first such system for hepatitis C virus (HCV) was only described in 2005. Since then, the development of a number of HCV trans ‐complementation models has improved our knowledge of HCV protein functions and interactions, genome replication and viral particle assembly. These models have also been used to produce defective viruses and so improvements are necessary for vaccine assays. This review provides an update on HCV trans ‐complementation systems, the viral mechanisms studied therewith and the production and characterization of trans ‐encapsidated particles.